Cationic porphyrins in the photoinactivation of viruses in blood - Santos, Patrícia da Silva (2021)
In the last years, besides the implementation of haemovigilance systems in many countries, the application of blood disinfection methods has been used in order to improve transfusion quality and safety. However, infections transmitted through blood transfusion still occur. The development of new methods to treat not only plasma and platelets, but also the whole blood and erythrocytes concentrates, can be an important measure to decrease the incidence of blood transfusion infections. Conventional disinfection techniques are currently in use essentially for plasma due to the collateral damage in cellular fractions. Antimicrobial photodynamic therapy (aPDT) represents an alternative to the conventional methods even for the whole blood and erythrocytes concentrates. aPDT involves the exposure of a photosensitizer (PS) to light in the presence of oxygen, which results in the production of reactive oxygen species (ROS) that causes irreversible damage in the pathogenic microorganisms. This therapy is already approved in some countries, but is limited to the use of three PSs, methylene blue (MB) for plasma disinfection and riboflavin and psoralen for plasma and platelet disinfection. The aim of this study was to evaluate the aPDT effect using cationic porphyrinic PSs (Tri-Py(+)-Me, Tetra-Py(+)-Me and Tetra-S-Py(+)-Me) in the photoinactivation of viruses in plasma and whole blood and the results were compared with the efficiency of an already approved PS to disinfect plasma, the MB. Possible side effects of aPDT on erythrocytes were also assessed by osmotic fragility tests of erythrocytes cytoplasmic membrane using increasing NaCl concentrations and erythrocytes count before and after aPDT treatment. The T4 bacteriophage was used as a model of mammalian viruses. For this purpose, a phage suspension of 108 PFU/mL in plasma and whole blood was exposed to white light (150 mW/cm2) for 270 minutes with a PS concentration of 10 μM. The results indicated that porphyrinic PSs were more effective than MB in the photoinactivation of T4 phage in plasma, with special emphasis of Tetra-S-Py(+)-Me. However, their efficiency decreased in the whole blood, possibly due to the aPDT blocking effects caused by the matrix complexity. None of the PSs tested caused osmotic stress and subsequent haemolysis in the erythrocytes at the isotonic condition. Therefore, porphyrinic derivatives, mainly the Tetra-S-Py(+)-Me, can be considered a promising PSs to photoinactivate viruses in plasma, but further improvements are required for aPDT use in whole blood.